(3OjhGf GdeTOs - (3GdeTO , Ydj Hf YeQ Hf bRd GdJQceGfj GdjGQhbj, Sja GdOjf,J (B656 (3g` s
(3ChdgG (B:s
(3bGd GdCejQ GdCLd GdYGde de CfXe GdTYQ eSJajOkG ef GdbhGaj hdG GdeYGfj s
(3BNQgG (B:s
(3deG QMdhG aHGf Yfj LdOj QhMj daQGbce JLGPH LSOj s
(3Vef eLehY , JQJjHgG (B: (3ef U (B91 - (3U(B181s
(3GfXQ GdLRA GdChd HQbe (B258 (3COHs
(3Ydi GdeLehYI Jedc SfI (B993(3g```s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B131s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B207 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B814s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs